Deubiquitination of MITF-M Regulates Melanocytes Proliferation and Apoptosis - Hu, Shuaishuai; Bai, Shaocheng; Dai, Yingying; Yang, Naisu; Li, Jiali; Zhang, Xiyu; Wang, Fan; Zhao, Bohao; Bao, Guolian; Chen, Yang; Wu, Xinsheng (Frontiers in Molecular Biosciences, 2021)
Microphthalmia-associated transcription factor-M (MITF-M) is the key gene in the proliferation and differentiation of melanocytes, which undergoes an array of post-translation modifications. As shown in our previous study, deubiquitinase USP13 is directly involved in melanogenesis. However, it is still ambiguous that the effect of USP13-mediated MITF-M expression on melanocytes proliferation and apoptosis. Herein, we found that MITF-M overexpressing melanocytes showed high cell proliferation, reduced apoptosis, and increased melanin levels. Besides, melanin-related genes, TYR, DCT, GPNMB, and PMEL, were significantly up-regulated in MITF-M overexpressing melanocytes. Furthermore, Exogenous USP13 significantly upregulated the endogenous MITF-M protein level, downregulated USP13 significantly inhibited MITF-M protein levels, without altering MITF-M mRNA expression. In addition, USP13 upregulation mitigated the MITF-M degradation and significantly increased the half-life of MITF-M. Also, USP13 stabilized the exogenous MITF protein levels. In conclusion, the MITF-M level was regulated by USP13 deubiquitinase in melanocytes, effecting melanocytes proliferation and apoptosis. This study provides the theoretical basis for coat color transformation that could be useful in the development of the new breed in fur animals.